Adoption d'une nouvelle réglementation sur les aides publiques à l'agriculture - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
Le 10 décembre 2003, l'UE a adopté une nouvelle...